Estações e Trilhos da Escola Livre de Teatro (ELT) de Santo André (SP) 1990-2000 - Leite, Vilma Campos dos Santos (2011)
2000) accompanies a decade in the trajectory of a theater school, the ELT, trying to bring up the ways of living the theatrical formation and creation, as well as the dialogues conducted with their time and place. Three lines make up the sources: written documents, images and interviews, being able to emphasize the last ones that allowed working from the concepts of memory, narrative and experience. The work uses the analogy of a train to conduct the path and it is divided in three stations. The First station Paranapiacaba (1990-1992) deals with the political and social moment present in the city of Santo André, that through a municipal administration of the Workers Party (PT) institutionalized a drama school, the ELT. In this station, are placed the dialogues and the barriers with the theatrical movement there stand, the strategies to the school composition, the conception, the experiences of the professionals who worked in ELT, highlighting the creation and setting of a show with a homonyms name to the station. The Second station Capuava points the experience lived by the students of the Actor Formation Nucleus, between 1990-1992, their creative process and the developments of their theatrical practices, in the period of 1993-1996, when the ELT was closed due to the switching of allegiances in the municipal government. The Third and last station Santo André treats the manner in which was lived the return of the ELT in 1997-2000. Stresses, also, the elaboration of a pedagogical tool, called collaborative process, which involves mainly the Dramaturgy and Directing Nuclei and that is in line with the theatrical making of the last decade, of the twentieth century, in the city of São Paulo and beyond it. Among the transformations, the dissolution of a broader cultural project in the artistic formation of the municipality, without meaning, necessarily, a conformation to a given reality. Regarding what continues, an appropriation of the creative making inside the own scene in a learning to learn through the experience and that the nonexistence of a previous curriculum favors. The artistic experiences of the professionals exist without dichotomy with the theatrical pedagogy. Therefore, the ELT fits in a genealogy of schools which think the theatrical formation while research and reformulation of the own doing.